The Practice of a Quality Assurance System in Open and Distance Learning: A case study at Universitas Terbuka Indonesia (The Indonesia Open University) - Belawati, Tian; Zuhairi, Amin (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
Quality assurance for distance higher education is one of the main concerns among institutions and stakeholders today. This paper examines the experiences of Universitas Terbuka (UT), which has initiated and implemented an innovative strategy of quality assurance (QA) for continuous improvement. The credo of the UT quality assurance system is "We write what we do. We do what we write. We check. We improve continuously!" Implementing a quality management system at the UT, a mega-university with a student body of more than a quarter of a million and which involved a network of participating institutions and regional centres, was a formidable task to accomplish. To achieve its lofty goal, UT adopted and contextualised the draft of the Asian Association of Open Universities (AAOU) QA Framework to launch its own quality assurance program. This has taken a great deal of commitment and participation of all staff involved. QA at the UT required systematic and step-by-step processes, including development of the QA framework and job manuals, raising awareness and commitment amongst all staff involved, internal assessment, and integration of QA programs into the university's annual action plans, external assessment and benchmarking. This paper concludes that quality assurance must be developed as institutional policy and strategy for continuous improvement.